Aerial wetting contact angle measurement using confocal microscopy. (26th October 2016) - Chesna, Jacob W; Wiedmaier, Bob F; Wang, Jinlin; Samara, Ayman; Leach, Richard K; Her, Tsing-Hua; Smith, Stuart T
Abstract: A method is presented in which the wetting contact angle of a sessile drop is acquired aerially using confocal techniques to measure the radius and the height of a droplet deposited on a planar surface. The repeatability of this method is typically less than 0.25°, and often less than 0.1°, for droplet diameters less than 1 mm. To evaluate accuracy of this method, an instrument uncertainty budget is developed, which predicts a combined uncertainty of 0.91° for a 1 mm diameter water droplet with a contact angle of 110°. For droplets having diameters less than 1 mm and contact angles between 15° and 160°, these droplets approach spherical shape and their contact angles can be computed analytically with less than 1% error. For larger droplets, gravitational deformation needs to be considered.